Equine Science - Rutland, Catrin; Rizvanov, Albert (Veterinary Medicine and Science, 2020)
Understanding the latest developments in equine science is essential for all veterinary and equine professionals and students, researchers, owners, and those caring for equids. This book reflects the diversity in research presently being carried out worldwide. From locomotion and the digestive system, through to the skin and reproduction. The chapter on medicine includes not only some of the latest advances in gene therapy but also reveals medieval treatments, providing a fascinating glimpse into the past whilst also looking at future technologies. The book also highlights some contemporary insights into diet and behavior. From DNA and individual cells through to the entire animal, this research uses different scientific methods to understand horses and donkeys in greater detail.